Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{a}{b}:\frac{c}{d}=\frac{a}{b}.\frac{c}{d}\Rightarrow\frac{a}{b}=\frac{a}{b}.\frac{c}{d}.\frac{c}{d}\Rightarrow\frac{a}{b}:\frac{a}{b}=\frac{c}{d}.\frac{c}{d}\)
\(\Rightarrow1=\left(\frac{c}{d}\right)^2\Rightarrow\frac{c}{d}=1\text{ hoặc }\frac{c}{d}=-1\)
\(\frac{a}{b}=\frac{c}{d}\)(\(b,d\ne0\))
\(\Leftrightarrow ad=bc\)
\(\Leftrightarrow2ad=2bc\)
\(\Leftrightarrow ad-bc=bc-ad\)
\(\Leftrightarrow ad-bc+ac-bd=bc-ad+ac-bd\)
\(\Leftrightarrow\left(a+b\right)\left(c-d\right)=\left(c+d\right)\left(a-b\right)\)
\(\Leftrightarrow\frac{a+b}{a-b}=\frac{c+d}{c-d}\)(\(a-b,c-d\ne0\))
Ta chỉ cần cộng thêm 1 vào mỗi tỉ số,
\(\frac{b+c+d}{a}+1=\frac{c+d+a}{b}+1=\frac{d+a+b}{c}+1=\frac{a+b+c}{d}+1\)
\(\frac{a+b+c+d}{a}=\frac{a+b+c+d}{b}=\frac{a+b+c+d}{c}=\frac{a+b+c+d}{d}\)
Vì a + b + c + d \(\ne\)0 nên a = b = c = d
\(\Rightarrow k=\frac{3a}{a}=3\)
Ta có:
a/b : c/d = a/b × c/d
=> a/b : a/b = c/d × c/d
=> (c/d)2 = 1
=> c/d = 1 hoặc -1